Kinetic Study on the Catalytic Pyrolysis of Decanter Cake from Palm Oil Milling Plant by using Thermogravimetry Data - Nugroho , Dewayanto; Ruzinah, Isha; Mohd Ridzuan, Nordin (Penerbit Universiti Teknologi Malaysia, 2014)
The kinetic study on the catalytic pyrolysis of decanter cake (DC) from palm oil milling plant was carried out using thermogravimetry method. Catalysts were added to dry DC in desired ratio and then mixed manually. Based on the thermogravimetric analysis (TGA) results, the main thermal decomposition of both non-catalytic and catalytic pyrolysis of DC occurred at 210–530°C. Coats-Redfern method was used in this study. Two stage reactions were identified during the main thermal decomposition, with the first stage at 210–330°C, while second stage occurred at 330–530°C. The pyrolysis reaction obeyed the first and second order kinetic model for first and second stage reaction, respectively. The presence of the catalysts reduced the activation energy of thermal decomposition in both stages. Minimum activation energy value was observed at 10 wt% of catalyst loading.